Efficacy and safety of gastric exposed endoscopic full-thickness resection without laparoscopic assistance: a systematic review - Granata, Antonino; Martino, Alberto; Amata, Michele; Ligresti, Dario; Tuzzolino, Fabio; Traina, Mario (Endoscopy International Open, 2020)
Background and study aims Exposed endoscopic full-thickness resection (Eo-EFTR) without laparoscopic assistance is a minimally invasive natural orifice transluminal endoscopic surgery (NOTES) technique that has shown promising efficacy and safety in resection of gastric submucosal tumors (G-SMTs) arising from muscularis propria (MP). However, data on the efficacy and safety of gastric Eo-EFTR mostly come from relatively small retrospective studies and concern regarding its use still exists. The aim of our systematic review was to assess the efficacy and safety of gastric Eo-EFTR without laparoscopic assistance.Methods A detailed MEDLINE and EMBASE search was performed for papers published from January 1998 to November 2019 and reporting on gastric Eo-EFTR without laparoscopic assistance. The search strategy used the terms “endoscopic full thickness resection” and “gastric” or “stomach”. The primary outcomes were complete resection and surgical conversion rates. The secondary outcomes were overall major adverse events, delayed bleeding, delayed perforation, peritonitis, abdominal abscess and/or abdominal infection and successful Eo-EFTR.Results Fifteen Asian studies were included in our final review, providing data on 750 Eo-EFTR-treated G-SMTs. The per-lesion rate of complete resection and surgical conversion were 98.8 %\0.8 %, respectively. The per-lesion rate of major adverse events, delayed bleeding, delayed perforation and peritonitis, abdominal abscess and/or abdominal infection was 1.6 %\0.5 %\0.1 %\0.9 %, respectively. The per-lesion rate of successful Eo-EFTR (i. e. complete tumor resection and effective endoscopic defect closure) was 98.3 %.Conclusions Eo-EFTR without laparoscopic assistance appears to be highly effective and safe NOTES for removing deep G-SMTs, particularly those arising from MP layer.